Proficiency testing results of CD4+ T cell determination in Thailand - Chairatanapiwong, Saowanit; Kulawong, Panida; Lawapakul, Puwadon; Pongpunyayuen, Panida; Klangsinsirikul, Phennapha (Journal of Associated Medical Sciences, 2025)
Background: CD4+ T cell number is an important marker for assessing immune status, differentiating the severity of infections, and monitoring treatment in patients infected with human immunodeficiency virus (HIV). The determination of the percentage and absolute count of CD4+ T cells plays an essential role in treatment decisions and in ongoing patient care. Consequently, this analysis must be highly effective, with proper quality control processes. Participation in proficiency testing is a key component of the quality system. Objectives: This study aimed to develop a proficiency testing program for CD4+ T cell analysis in Thailand. Materials and methods: Two proficiency testing materials were prepared and assigned the numbers CD4-01, which was low level, and CD4-02, which was normal level. PT materials were tested for the four following parameters: %CD3+ cells, CD3+ cell count, %CD4+ T cells, and CD4+ T cell count in 39 participating laboratories. Performance assessment of the laboratories was shown as a z score according to the ISO13528:2022 standard. Results: Proficiency testing materials met the acceptable criteria for homogeneity and stability according to ISO13528:2022. As due to uncertainty of assigned values are smaller than 0.3σpt, the performance of participating laboratories was assessed using a z score. More than 89 percent of participated laboratories demonstrated acceptable performance across all four parameters, while less than six percent were classified as within the warning signal range, and less than eight percent were deemed unacceptable. The causes of unacceptable performance included inappropriate instrument settings, inadequate compensation, and issues with gating techniques. Conclusion: Proficiency testing materials for CD4+ T cell determination were satisfactorily prepared and met the criteria for homogeneity and stability according to ISO13528:2022. The results of the pilot study conducted in 39 laboratories showed that more than 87 percent of the results were within acceptable range.